ANALISIS WAKTU TUNGGU PELAYANAN RADIOLOGI DI RUMAH SAKIT SYARIF HIDAYATULLAH TAHUN 2018 - Putri Amanah; Mustakim - - (Dian Nuswantoro Semarang, 2020)
Radiology services as integrated parts of health services as a whole are part of the community's need for health services. Therefore, the radiology services should provide quality services. The study was a descriptive analytic research with qualitative and quantitative approaches or mix method that used data collection in the form of waiting time duration for radiology services, in-depth interviews, observation, and document review. Sampling using proposition estimation with random sampling technique with the number of 106 patients. The informants in primary data collection at the Radiology Installation at Syarif Hidayatullah Hospital were the head of the radiology installation, radiology specialist, head of the radiology and radiographers unit.The average waiting time duration for radiology services is 4 hours 59 minutes. The result has not met Kepmenkes Standard No.129/Menkes/SK/II/2008, which is ? 3 hours. The standard of waiting time duration for radiology service is not met the rule regarding to there is no doctor who is the standby or full timer while the radiology service to the patient is given for 24 hours.It is expected that Syarif Hidayatullah Hospital has teleradiology which can be used as a solution to meet the waiting time duration for radiology services, especially the reading of photos and expenditure of expedition results and can meet the quality of services that appropriate to the standards.Keywords: waiting time duration, radiology services